(untitled) (E Global Congress, 2024)
This article highlights the importance of metrological support in yarn spinning enterprises, examining how it impacts production processes and contributes to improving product quality. It combines scientific principles with practical recommendations, focusing on innovative approaches to optimize production efficiency.